The role of transformational leadership in enhancing Islamic work ethic and employee engagement - Fatmah, Dinda; Putri , Karina Ananda; Rahmah, Mirhamida; Purnama, Chamdan; Hasani, Syaiful; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study investigates the relationship between Islamic work ethic, job satisfaction, and employee engagement, with transformational leadership as a moderating variable. It aims to assess whether job satisfaction mediates the impact of Islamic work ethic on engagement and if transformational leadership enhances these effects. The research offers insights into how ethical values and leadership styles influence employee engagement at Brangkal Printing. Method – A quantitative approach with a cross-sectional survey design was used, involving all 75 employees at Brangkal Printing through total sampling. Data were gathered using a likert-scale questionnaire to measure Islamic work ethic, job satisfaction, transformational leadership, and employee engagement. The data analysis technique used in this study is partial least squares structural equation modeling (PLS-SEM). Findings – The results reveal that the Islamic work ethic does not directly influence employee engagement but positively impacts job satisfaction, which enhances engagement, confirming the mediating role of job satisfaction. Transformational leadership directly affects engagement but does not significantly moderate the relationships examined. Implications – This research highlights the significance of the Islamic work ethic in improving job satisfaction and engagement while highlighting the context-dependent nature of transformational leadership. It extends existing theories by emphasizing the influence of cultural and ethical values on workplace behavior. Organizations should enhance job satisfaction through a supportive work environment, fair compensation, and career development. Integrating Islamic values into leadership strategies can optimize employee motivation, commitment, and engagement, leading to better performance.